1986
DOI: 10.1007/bf00174371
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cataleptogenic effects of potentized homoeopathic drugs

Abstract: The four homoeopathic drugs, Gelsemium, Cannabis Indica, Graphites and Agaricus Muscarius, administered orally in 30th and 200th potencies on white rats, enhanced restraint-induced catalepsy in a similar manner to the two standard drugs pilocarpine and haloperidol (IP injection at 5 mg/kg). All the drugs tested differed from each other in the duration of cataleptogenic effect, which was more prolonged with Cannabis, Graphites and Agaricus than with Gelsemium and the two non-homoeopathic drugs used. The 200th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…Other interesting and varied studies have been reported by the group of Sukul, 16 involving the use of four homeopathic remedies (Gelsemium, Cannabis indica, Graphites and Agaricus muscaris) administered orally to albino rats in potencies of 30CH and 200CH. All four remedies augmented the cataleptic effect induced by restriction of movement (restraint) in a similar manner to the reference compound haloperidol (i.p.…”
Section: Catalepsy and Convulsion Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other interesting and varied studies have been reported by the group of Sukul, 16 involving the use of four homeopathic remedies (Gelsemium, Cannabis indica, Graphites and Agaricus muscaris) administered orally to albino rats in potencies of 30CH and 200CH. All four remedies augmented the cataleptic effect induced by restriction of movement (restraint) in a similar manner to the reference compound haloperidol (i.p.…”
Section: Catalepsy and Convulsion Modelsmentioning
confidence: 96%
“…Another reason for undertaking a systematic experimental trial of Gelsemium was that this remedy is frequently used in humans for anxiety symptoms, and has already been investigated in studies by other authors which do not, however, always report consistent results. 13,14,16,18,23 In experimental research in homeopathy it is especially important to consolidate new and preliminary data -which can often be unexpected or even contrary to the beliefs of official pharmacology -through statistically solid evidence. We conducted two complete series of experiments testing various Gelsemium dilutions, Assays of homeopathic remedies in rodents P Bellavite et al with small changes and adaptations of methodology: in the first series -the results of which have been recently published 31 and here are further detailed -the LD test was performed the day before the OF on animals (from Harlan Laboratories), which were housed 4 per cage; in the second series of studies (Magnani et al, manuscript in preparation, whose preliminary data are here reported) the LD test was performed the day after the OF test on animals (from Charles River Laboratories), which were housed 2 per cage.…”
Section: Screening Of Six Homeopathic Remediesmentioning
confidence: 98%
“…Other laboratories have also reported in vivo [16,19,28,29] or in vitro [30] effects of Gelsemium s. in extremely low doses or high dilution/dynamization, but its action at the cellular level has not been fully clarified. To follow up the above evidence of an anxiolytic effect in animal models, we decided to investigate the Gelsemium s. mechanism of action in neuronal models by assessing the drug effects on whole genome expression changes.…”
Section: Introductionmentioning
confidence: 99%
“…65 Time factors and prior history also play roles in the direction of effects with homeopathic remedies in animal and cellular models. 22,33,37,66,67 Similarly, seasonal variants (e.g., pollen, temperature, light cycle, and barometric pressures), undocumented differences in menstrual cycles for female participants, or external stress levels for individual subjects over time (e.g., examination-related stress periods in students) could have could each also have confounded the current findings. However, none of those confounding factors was systematically built into the design of this exploratory study.…”
Section: Discussionmentioning
confidence: 89%